2021
DOI: 10.1002/app.50925
|View full text |Cite
|
Sign up to set email alerts
|

Using conjugated system from natural sources for the synthesis of sulfur copolymers by bi‐function catalysts at mild temperatures

Abstract: Sulfur‐rich polymers are promising materials to cover several applications including mercury capture adsorbents. Tung oil, a natural conjugated triene triglyceride oil, were selected to prepare sulfur‐rich copolymers. The unique second monomer made reaching the gel point possible at a mild temperature of 130°C in 2.5 h. The reaction accomplishment was confirmed by the depletion of double bonds in tung‐oil‐sulfur copolymers measured by 1H NMR, FTIR, XRD, and DSC. A bi‐function catalyst calcium hydroxide acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The inverse vulcanization system is tung oil, for which it was found that its unique conjugated triene tremendously decreased reaction temperature compared with the non-conjugated double bonds in normal lipids like sunflower oil. 29 The experimental results obtained from particular reaction conditions would reflect whether trace impurities are beneficial or detrimental to the copolymerization and provide evidence to confirm or disprove the mechanisms proposed by other researchers.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…The inverse vulcanization system is tung oil, for which it was found that its unique conjugated triene tremendously decreased reaction temperature compared with the non-conjugated double bonds in normal lipids like sunflower oil. 29 The experimental results obtained from particular reaction conditions would reflect whether trace impurities are beneficial or detrimental to the copolymerization and provide evidence to confirm or disprove the mechanisms proposed by other researchers.…”
Section: Introductionsupporting
confidence: 60%
“…Others in our research group demonstrated that sunflower oil does not polymerize with S 8 at 130°C. 29 To confirm the initiating role of conjugated trienes in tung oil, a mixed vegetable oil with 50% tung oil (1 g) and 50% sunflower oil (1 g) was used to react with sulfur (2 g). Experiments showed that mixed vegetable oil reacted with sulfur at 130°C, and produced poly (S50-TO-50-SFO) which was lighter in color and softer in texture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lyu et al introduced Ca(OH) 2 as a catalyst for inverse vulcanization, which could reduce the polymerization time, increase the conversion yield of sulfur and act as a porogen agent through copolymerization of tung oil with sulfur. 126 For instance, at an oil : sulfur ratio of 1 : 1, the reaction could be completed in 30 min and the amount of free sulfur in the polysulfide was reduced to zero. A comparison of the removal rate of Hg 2+ from HgCl 2 solutions (2000 mg L −1 ) showed that the porous polysulfides prepared in the presence of Ca(OH) 2 could remove up to 75% of Hg 2+ , whereas the value for non-porous polysulfides was around 65%.…”
Section: Natural Product Derived Polysulfidesmentioning
confidence: 99%